2015
DOI: 10.1007/978-3-319-19773-9
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Education

Abstract: Abstract. Peer assessment has become popular in recent years. However, in peer assessment, a problem remains that reliability depends on the rater characteristics. For this reason, some item response models that incorporate rater parameters have been proposed. However, in previous models, the parameter estimation accuracy decreases as the number of raters increases because the number of rater parameters increases drastically. To solve that problem, this article presents a proposal of a new item response model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…This large difference is most likely due to the fact that our recent study involved students at a regular, urban middle school whereas the other study involved students at a magnet school for high-achievers. Although it is difficult to quantitatively compare the transition results from [12] to these new results because the cluster centroids are different, the results are fairly qualitatively consistent. In both studies, there were more transitions to the same cluster (i.e., non-transitions) than would be predicted by a random model.…”
Section: Comparison To Previous Worksupporting
confidence: 58%
See 2 more Smart Citations
“…This large difference is most likely due to the fact that our recent study involved students at a regular, urban middle school whereas the other study involved students at a magnet school for high-achievers. Although it is difficult to quantitatively compare the transition results from [12] to these new results because the cluster centroids are different, the results are fairly qualitatively consistent. In both studies, there were more transitions to the same cluster (i.e., non-transitions) than would be predicted by a random model.…”
Section: Comparison To Previous Worksupporting
confidence: 58%
“…We modeled the students' behavior with coherence analysis-based metrics [7] and clustered the resulting feature vectors to reveal commonalities in their problem solving approaches. We compared the resulting clusters to those in a different study [12] and we identified four of the five student learning behavior clusters found by that research. The missing cluster, engaged and efficient students, was likely missing due to the different student populations at the magnet school.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This new learning environment is enriched with digital, adaptive and context-aware resources that can provide personalized and inclusive learning experiences to enhance teaching and learning in an online learning paradigm [3][4][5]. The students can use a smart learning environment and digital learning devices to support their learning strategies in order to enhance their learning experiences in an online learning environment, and one such strategy is self-regulated learning (SRL), which is defined as selfgenerated thoughts, feelings, and actions that are planned and cyclically adapted to the attainment of personal learning goals in a subject [6]. It is well established that students' ability to self-regulate their learning process can enhance skill and performance [7,8].…”
Section: A Backgroundmentioning
confidence: 99%
“…The smart learning environment is a responsive, proactive, and context-aware learning environment. Therefore, it is of interest to explore how SRL can support a learner to develop thinking strategies and promotes metacognitive and motivations towards achieving learning goals (Pérez-Álvarez et al, 2018;Durán-Sánchez et al, 2018;John et al, 2015;Zimmerman, 2002). The student's ability to control their learning process can enhance the educational process and provide the support needed to succeed in an online learning environment (Pérez-Álvarez et al, 2018;Spector, 2016;Zimmerman, 2002).…”
Section: Introductionmentioning
confidence: 99%